Maintaining the Free Flow of Information. A Manifesto-like Intervention for Practice-Based Research in Academic Training Programs for Multimedia Journalism - Evelyn Echle (VIEW Journal of European Television History and Culture)
With a changing media landscape in mind, this article takes a closer look at academic training standards for journalists. Focusing on multimedia production and innovative science, it analyses the impact on business models, resources and working conditions. As an interventionist appeal, it argues in favour of practice-based research and new training methods. Key demands include a greater awareness of the democratic role of journalism, ethical sensitivity and sustainable funding. By interweaving theory, practice and politics, this Manifesto-like paper aims to strengthen the profession of journalism and build a bridge between academia and practical training.